(MOLDING DESIGN OF PADANG STATE POLYTECHNIC LOGO SOUVENIR MOLDING ON PRESSED PLASTIC INJECTION MOLDING MACHINE 1,960 KG / CM²) - Alfian Alfian (Jurnal Ilmiah Poli Rekayasa, 2021)
ABSTRACT Padang State Polytechnic has been established since 1987 under the name Polytechnic Engineering and then changed its name several times to the management policy by Andalas University then, until now it is independent until now with the name Padang State Polytechnic. The 33-year-old polytechnic of the Padang State Polytechnic establishment must have an icon, symbol and trinkets that have PNP characteristics so that they are easy to recognize and remember. Souvenirs are a form of applying media for promotion and souvenirs for people who already know and come to Padang State Polytechnic. Plastic injection molding machine is a machine used to mold plastics with a basic material in the form of plastic pellets. Plastic injection molding machine is the process of processing plastic material in the form of seeds which are heated until they become liquid and then injected into the molding which then freezes / hardens according to the shape of the mold. The products produced by injection molding machines vary, from electronic tools, automotive tools, home appliances, plastic souvenirs, to tableware. The success of the resulting product is highly dependent on Molding. The plastic injection molding machine has parts, namely the Injection Unit, Molding Unit and Clamping Unit. The Injection Unit and Clamping Unit are the most important parts in the manufacturing process of plastic products where the control operation is executed on the control panel found on the plastic injection molding machine. The control panel on the machine can adjust the amount of clamping pressure, stroke length, plastic volume, and temperature used. The molding unit is the main part of the plastic product manufacturing process. Mold (mold) is a tool / tool used to make products according to the desired design (shape and dimensions). Plastic molding has its respective functions, parts of the mold, namely Cavity and Core, Sprue, Runner and Gate, Undercut. The printing process on a Plastic Molding machine has several stages such as the cutting process, mold safety and machine safety, execution, product check, setting, execution, and final. Materials used in the Plastic Molding process are usually materials that are often used daily and are safe for use by all groups, such as Polyproplene, Polycarbonate, and High Density Poly Ethylene. The product that will be produced from the molding made is a key toy souvenir made of plastic, with a shape like the Padang State Polytechnic logo, measuring 6 cm long, 6 cm wide and 5 mm thick. The test results obtained will be shown through field applications, socialization at the Padang State Polytechnic and writing in national journals are the targets and outputs of this novice lecturer research activity. Keywords— Mold, Souvenir, Cavity, Core, Pnp.